A STUDY OF A SECOND GENERATION KOREAN-AMERICAN IN COPING WITH HER IDENTITY AS PORTRAYED IN MINOR FEELINGS: AN ASIAN AMERICAN RECKONING BY CATHY PARK HONG - Susilowati, Fransisca Leony; Margono, Yosep Bambang (LINGUAMEDIA Journal, 2024)
In this thesis, the writer  discuss two things related to the identity of the second-generation of Asian-American in America. First, the writer analyzing: What factors caused Cathy Park Hong to feel struggle to prove her identity and existence as a second generation of Korean-American in her society. The first is how does Cathy Park Hong's society make her feel struggled to prove her identity and existence as a second generation of Korean-American in Americar? Then the second is how does she overcome problems of her identity and existence as a Korean-American in her society in America. In this research, the writer uses qualitative descriptive research. This study uses data in the form of writing and descriptions of the data sources that have been collected. At the end of this thesis the writer concludes that: Hong has difficulty proving the existence of her ethnic identity as a Korean-American because she is too often traumatized by being abandoned by other people. Ethnicity and also often feel underappreciated by other ethnicities. Hong, in dealing with the problems she faces, prefers to store and vent her feelings of sadness into poetry.